2012
DOI: 10.1080/10286632.2011.625420
|View full text |Cite
|
Sign up to set email alerts
|

Web communication can help theaters attract and keep younger audiences

Abstract: This paper focuses on the use of web communication tools as a policy device to regulate access to theaters. By comparing the profile of what we call 'techsavvy' spectators (i.e. audience using the website of a theater) with the profile of the general audience we examine whether the web can be regarded as an effective tool to address regular spectators or to reinforce the participation of different segments within the audience. The study suggests that the web appears to be the favorite direct marketing tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…MacMillan et al, 2005;Saxton et al, 2007). In recent years, non-profit organizations have been primarily resorting to a unidirectional transmission of information to their clients (Turrini et al, 2011). The problem with such a one-way communication traffic is that clients are deprived of the opportunity to be heard by the company whenever the need to voice out something arises, which could negatively affect company-customer relationship.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MacMillan et al, 2005;Saxton et al, 2007). In recent years, non-profit organizations have been primarily resorting to a unidirectional transmission of information to their clients (Turrini et al, 2011). The problem with such a one-way communication traffic is that clients are deprived of the opportunity to be heard by the company whenever the need to voice out something arises, which could negatively affect company-customer relationship.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…That same study also reported that two-way communication is crucial in the relationship marketing process. In line with these findings, marketing strategies and tactics in the performing arts pursue three goals: first, providing the audience with more information about the program; second, enabling transactions like online ticket purchase or donations; and finally, fostering a two-way-interaction between the audience and the organization (Saxton et al, 2007, Turrini et al, 2011. Hence:…”
Section: Relationship Marketing Tacticsmentioning
confidence: 85%
See 1 more Smart Citation
“…Answers vary, however, as to what experiences audiences seek and how organizations could provide these. Strategies proposed include providing opportunities for more active audience engagement (Brown & Novak-Leonard, 2011;Conner, 2013;Glow, 2013;Pulh, Marteaux, & Mencarelli, 2008); performing in non-traditional venues (Walker & Sherwood, 2003;Reidy, 2014); creating a more welcoming, social, and/or informal environment (Brown & Ratzkin, 2013;Pulh, Marteaux, & Mencarelli, 2008; on socializing as a motivation see National Endowment for the Arts, 2015b; Ostrower, 2008); making increased use of technology and digital media (Bakhshi & Throsby, 2012;Preece, 2011;Turrini, Soscia, & Maulini, 2012;Walmsley, 2016); and better understanding audiences through market research (Grams, 2008;Harlow, 2014).…”
Section: Summary Of Findings From the Review Of Literature On Audience Buildingmentioning
confidence: 99%
“…Natomiast za najbardziej wartościową publikację, ze względu na badany serwis internetowy, uznano The Royal Opera House Website Evaluation Report (Trosheva, 2013). W projektowaniu własnej procedury badawczej przydatne okazały się publikacje dotyczące komunikacji teatru z widzami, w tym badanie nawyków konsumenckich związanych z nabywaniem biletów na spektakle oraz rola emocji w tym procesie (Troilo et al, 2014), komunikacja teatru z publicznością za pomocą Internetu (Turrini et al, 2012), strategia pozyskiwania widzów teatralnych z wykorzystaniem narzędzi komunikacji cyfrowej (Kossecki & Świerczyńska-Kaczor, 2014) oraz badanie publiczności i wizerunku teatrów warszawskich (Siwiak et al, 2013).…”
Section: Stan Badańunclassified